The mythoworld of flora symbols in the text of Ukrainian exorcisms (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Some functioning peculiarities and symbols meanings of the vocabulary on the marking of floralexemes in the Ukrainian exorcisms text are analyzed in the article. Some wild and cultivated plants in the magic space of the investigated texts are defined. Some meanings of the names of plants and their transformation into magic creatures attributes and independent characters are considered.
Keywords: text; exorcism; symbol; the names of plants; floralexemes; mythoworld; semantics